Serum cytokine profiles as predictors of asthma control in adults from the EGEA study. (April 2017) - Akiki, Zeina; Rava, Marta; Diaz Gil, Oscar; Pin, Isabelle; le Moual, Nicole; Siroux, Valérie; Guerra, Stefano; Chamat, Soulaima; Matran, Regis; Fitó, Montserrat; Salameh, Pascale; Nadif, Rachel
Abstract: Background: To which extent serum cytokines may predict asthma control in adults remains understudied. Objectives: We investigated cross-sectional and longitudinal associations between cytokine profiles and asthma outcomes. Methods: Serum interleukin (IL)-1Ra, IL-5, IL-7, IL-8, IL-10, IL-13 and TNF-α levels were determined in 283 adults with current asthma from the 2nd survey of the Epidemiological Study on the Genetics and Environment of Asthma (EGEA2). Participants were followed-up seven years later. Asthma symptom control was assessed according to GINA 2015 guidelines. Cytokine profiles were identified by principal component (PC) analyses, and expressed as above/below the median. Results: The first two PCs captured 82.5% of the variability. While all seven cytokines scored high on PC1, only IL-1Ra and IL-10 scored high on PC2. At EGEA2, neither PC1 nor PC2 were related to exacerbations, asthma attacks, asthma symptom control, lung function, or allergic diseases. High level of PC1 (above the median) was associated with higher blood neutrophil counts (P = 0.02), while high level of PC2 was associated with lower IgE levels (P = 0.04). High level of PC2 at EGEA2 was associated with lower bronchial hyperresponsiveness (adjusted(a) OR[95%CI] = 0.46[0.23; 0.91]) and with subsequent lower risk of worsening asthma control and attacks (aOR[95%CI] = 0.24[0.09; 0.60]; 0.31[0.11; 0.85] respectively). Conclusions: Serum cytokine profiles with high levels of IL-1Ra and IL-10 were associated with lower subsequent risks of worsening asthma control and attacks in adults. This study adds new findings for the role of serum cytokine profiles to help identifying adults with subsequent risk of asthma burden that could be targeted for specific therapies. Highlights: Among participants with asthma, two profiles of serum cytokines were identified. High IL-1Ra/IL-10 level was prospectively associated with lower risk of worsening asthma control. Results may contribute to improve patient classification to target them for therapy.